"Celeiro Catarinense": a agricultura e a paisagem do Oeste de Santa Catarina nos planos desenvolvimentistas (1968-1979) - Andrioli, Marina (2020)
This paper analyzes the emergence and consolidation of the idea of Celeiro Catarinense (state of Santa Catarina's barn,, more specifically, addressing the political-institutional relations that culminated in the consolidation of incentives for the development of agriculture in the region in the 1970s. This strategy was developed during the period known as the "economic miracle" - an attempt to carry out structural reforms during the civil-military dictatorship -, which has its governance basis in the National Development Plans (PND's). We will seek for sources that make it possible to understand the construction of structures for social, political and environmental transformation in the region, in an expanded perspective that considers not only the symbolic character, but that reveals the complexity to which the region was subjected. In addition to a reflection of the current political discourse, this work is committed to the bibliographic analysis of the documents produced in that period, which include maps, magazines, newspapers and photos, in the search for elements that complement the understanding of the formation of this region, as well as the consequences of human intervention in the landscape.